Young investigator challenge: MicroRNA‐21/MicroRNA‐126 profiling as a novel tool for the diagnosis of malignant mesothelioma in pleural effusion cytology. Issue 1 (14th January 2016) - Cappellesso, Rocco; Nicolè, Lorenzo; Caroccia, Brasilina; Guzzardo, Vincenza; Ventura, Laura; Fassan, Matteo; Fassina, Ambrogio
Abstract : BACKGROUND: In pleural effusion cytology, the distinction of malignant mesothelioma (MM) from reactive mesothelial cells (RMCs) may be challenging, even with the aid of immunocytochemistry or fluorescence in situ hybridization. It has been demonstrated that several microRNAs (miRNAs) are useful for this purpose in cell lines and histologic samples. In the current study, the authors evaluated the utility of an miRNA‐based classifier as a complement to cytology. METHODS: Quantitative reverse transcriptase‐polymerase chain reaction analysis of 15 miRNAs was performed in mesothelial (MET‐5A) and MM (H28 and H2052) cell lines. Significant miRNAs were validated in 51 MM and 40 nonneoplastic pleural histologic samples and then were tested in 29 MM and 24 RMC cytologic specimens. The performance of individual and combined miRNAs was assessed for their ability to differentiate between MM and RMCs. RESULTS: MiRNA‐19a (MiR‐19a), miR‐19b, miR‐21, miR‐25, and miR‐126 were differentially expressed in cell lines and histologic samples. MiR‐126 was down‐regulated in MM surgical specimens compared with nonneoplastic specimens, whereas all of the other miRNAs were overexpressed. In cytologic specimens, all miRNAs except miR‐25 were confirmed, exhibiting a sensitivity or a specificity higher than the threshold of 0.80, as recommended by the International Mesothelioma Interest Group. The best classifier resulted from the combination of miR‐21 and miR‐126, which achieved 0.86 sensitivity and 0.87 specificity. CONCLUSIONS: Subject to validation of the current results in further larger studies, miR‐21 and miR‐126 profiling could be an effective and reliable tool for the diagnosis of MM in pleural effusions complementary to cytology evaluation. Cancer (Cancer Cytopathol) 2016;124:28‐36. © 2016 American Cancer Society . Abstract : MicroRNA (miR) expression profiling identifies the miR‐21/miR‐126 signature as a novel diagnostic classifier for malignant mesothelioma in pleural effusion cytology. Such profiling may be a promising diagnostic tool that could be a valid aid for cytopathologists in the distinction between malignant mesothelioma and reactive mesothelial cells.